Determinants of Digital Technology Adoption in Indonesian Government: A Cross-Sectional Study of Government Accountants - Mis Fertyno Situmeang (Jurnal Dinamika Akuntansi dan Bisnis, 2025)
This study examines the determinants of digital technology adoption in the Indonesian government. Using a stratified random sampling technique, 487 government accountants from ministries, national agencies, and subnational governments were selected as research participants. Data were analysed using PLS-SEM to assess the individual, organizational, and environmental factors influencing digital technology adoption. The findings indicate that adoption is shaped primarily by individual-level factors, with perceived usefulness and technology readiness emerging as the strongest predictors. Organizational enablers, particularly managerial support and technological infrastructure, also contribute significantly, although resource limitations remain major constraints.